THE EFFECT OF LIQUIDITY, PROFITABILITY, FIRM SIZE, AND CAPITAL STRUCTURE ON STOCK PRICES OF IDX30 COMPANIES FOR THE 2019–2023 PERIOD - Tenny Afriani Sari; Said; Astrid Dita Meirina Hakim (Asosiasi Dosen Muda Indonesia, 2025)
This study investigates the effect of liquidity, profitability, firm size, and capital structure on stock prices of companies included in the IDX30 index during the period under review. Using a quantitative approach, multiple linear regression was employed to analyze secondary data obtained from annual reports and financial statements. The analysis reveals that liquidity and capital structure have a positive and significant influence on stock prices, indicating that higher current ratios and optimal debt levels tend to enhance market valuation. In contrast, profitability and firm size show no significant impact, suggesting that these variables may not be primary determinants of stock price movements within the observed sample. The results support the signaling theory and capital structure theory while offering practical insights for investors and corporate managers in formulating strategies to optimize firm value. These findings contribute to the literature on capital market performance in emerging economies.